Children of mothers being released from incarceration: characteristics and potential targets for intervention. Issue 4 (3rd July 2016) - Menting, Ankie T. A.; Orobio de Castro, Bram; Matthys, Walter
Abstract: Incarcerated mothers and their children may face a multitude of problems. To identify possible targets for intervention, more clarity is needed about characteristics of these children and their mothers. This study examined children's life events, behaviour problems and social cognitions and mothers' parenting behaviours as potential targets for intervention with mothers being released from incarceration, in the Netherlands with a culturally diverse sample. Participants were 121 children of mothers being released from incarceration and 63 children of comparison mothers from disadvantaged areas, without a history of incarceration. Children of mothers being released from incarceration were more disadvantaged in life events, had more behaviour problems, and their mothers' parenting behaviours were characterized by lower involvement and poorer monitoring compared with children of comparison mothers. Suboptimal parenting behaviours of mothers being released from incarceration were statistically associated with children's behaviour problems. Hence, these children face more difficulties that may contribute to problematic development than children from another at-risk population.